Assessment of genotoxic effects and changes in gene expression in humans exposed to formaldehyde by inhalation under controlled conditions - Zeller, Jasmin; Neuß, Simone; Müller, Jörg U.; Kühner, Stefanie; Holzmann, Karlheinz; Högel, Josef; Klingmann, Christoph; Bruckner, Thomas; Triebig, Gerhard; Speit, Günter (Mutagenesis, 2011)
Forty-one volunteers (male non-smokers) were exposed to formaldehyde (FA) vapours for 4 h/day over a period of five working days under strictly controlled conditions. For each exposure day, different exposure concentrations were used in a random order ranging from 0 up to 0.7 p.p.m. At concentrations of 0.3 and 0.4 p.p.m., four peaks of 0.6 or 0.8 p.p.m. for 15 min each were applied. During exposure, subjects had to perform bicycle exercises (∼80 W) four times for 15 min. Blood samples, exfoliated nasal mucosa cells and nasal biopsies were taken before the first and after the last exposure. Nasal epithelial cells were additionally sampled 1, 2 and 3 weeks after the end of the exposure period. The alkaline comet assay, the sister chromatid exchange test and the cytokinesis-block micronucleus test were performed with blood samples. The micronucleus test was also performed with exfoliated nasal mucosa cells. The expression (mRNA level) of the glutathione (GSH)-dependent formaldehyde dehydrogenase (FDH, identical to alcohol dehydrogenase 5; ADH5; EC 1.2.1.46) was measured in blood samples by quantitative real-time reverse transcription-polymerase chain reaction with TaqMan probes. DNA microarray analyses using a full-genome human microarray were performed on blood samples and nasal biopsies of selected subgroups with the highest FA exposure at different days. Under the experimental conditions of this study, inhalation of FA did not lead to genotoxic effects in peripheral blood cells and nasal mucosa and had no effect on the expression of the FDH gene. Inhalation of FA did also not cause alterations in the expression of genes in a microarray analysis with nasal biopsies and peripheral blood cells.